Tell me everything - Coman, Carolyn ([New York] : Farrar, Straus & Giroux, 1995)
After her mother dies in a rescue mission on a snowy mountain, twelve-year-old Roz wonders if talking to God, and to the boy for whom her mother died, can help her understand what happened.
"Aerial fiction."
Keywords: Death -- Fiction; Mothers and daughters -- Fiction; Christian life -- Fiction